Durford Abbey - Aldsworth, Frederick G. (Sussex Archaeological Collections, 1979)
Keywords: durford

Die Inkunabeln der Abtei La Vid - Backmund, Norbert (Analecta Praemonstratensia, 1979)
Keywords: la vid

Histoire de l'abbaye Sainte-Marie-de-Fontcaude et de ses bienfaiteurs - Barthès, Henri (H. Barthés, 1979)
Keywords: fontcaude

Die ehemalige Prämonstratenserkirche Neustift, jetzt Pfarrkirche St. Peter und Paul in Freising - Benker, Sigmund (Kleine Kunstführer, 1979)
Keywords: neustift

Ein Teil des Klosterarchives Bellelay liegt in Biel - Bloesch, Paul (Neues Bieler Jahrbuch, 1979)
Keywords: bellelay

Les constructions de l'ordre de Prémontré en France aux XVIIe et XVIIIe siècles - Bonnet, Philippe (École nationale des chartes, 1979)
Keywords: 🇫🇷 france (general)

Extrait de l'obituaire de Marcheroux - Brouette, Émile (Analecta Praemonstratensia, 1979)
Keywords: marcheroux

Ellen, Kreis Düren. Geschichte d. Dorfes u. d. Klosters d. Prämonstratenserinnen - Candels, Heinrich; Dauber, Reinhard (Veröffentlichungen des Bischöflichen Diözesanarchivs Aachen, 1979)
Keywords: ellen

Apunt sobre el Monastir de Bellpuig - Català, Pic Pere (Els castells catalans, 1979)
Keywords: bellpuig de las avellanes

De kerk van het Norbertinessenklooster te Rekem - Claassen, A.; Janssen, L. (Het Oude Land van Loon, 1979)
Keywords: rekem

Hermann von Scheda, Opusculum de conversione sua. Ein Beitrag zur jüdisch-christlichen Auseinandersetzung im Mittelalter - Drabek, Anna Maria (Kairos: Zeitschrift für Religionswissenschaft und Theologie, 1979)
Keywords: 👤 hermann of cologne

Abbaye Notre-Dame d'Ardenne: Calvados - Fournée, Jean (Collection des monographies de l'année des abbayes normandes, 1979)
Keywords: ardenne

Abbaye Notre-Dame de l'Isle-Dieu - Fournée, Jean (Abbayes et prieures de Normandie, 1979)
Keywords: isle-dieu

Abbaye Notre-Dame de Silly - Fournée, Jean (Abbayes et prieures de Normandie, 1979)
Keywords: silly

L'abbaye de Belle-Étoile. 3: Les paroisses de l'abbaye de Belle-Étoile - Fournée, Jean (Le pays bas-normand, 1979)
Keywords: belle-étoile

L'abbaye Saint-Jean de Falaise (Calvados) - Fournée, Jean (Abbayes et prieures de Normandie, 1979)
Keywords: falaise

L'abbaye de Bellozanne - Fournée, Jean; Le Bertre-Turban, Odile (Abbayes et prieurés de Normandie, 1979)
Keywords: bellozanne

Gräber und Grundmauern in der Marienkirche Gelnhausen - Frey, Gernot (Gelnhäuser Geschichtsblätter, 1979)
Keywords: gelnhausen (marienkirche)

Die Praemonstratenser in Köln und Dünnwald - Gehle, Burkhard (Analecta Praemonstratensia, 1979)
Keywords: dünnwald

Das Kloster Himmelspforte in Wyhlen und das Gnadenbild der "Maria im Buchs" - Gerspach, Hansjörg (Der Buchswald bei Grenzach, 1979)
Keywords: himmelspforte (germany)

Recente studies over de Vita metrica Norberti door Capgrave (1393-1464) - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1979)
Keywords: 👤 john capgrave; 👤 norbert of xanten

Kloster Hopels - Heckmann, Erich (Der Historien-Kalender, 1979)
Keywords: hopels

Stift und Kartause zu Eppenberg - Heimerich, Gisela (Quellen und Abhandlungen zur Geschichte der Abtei und der Diözese Fulda, 1979)
Keywords: eppenberg

A History of Halesowen Abbey - Hunt, J.A. (s.n., 1979)
Keywords: halesowen

Zur Geschichte der Abtei Wadgassen während des Schismas - Jank, Dagmar (Zeitschrift für die Geschichte der Saargegend, 1979)
Keywords: wadgassen

Anthropologisch en paleopathologisch onderzoek van de beenderresten, gevonden bij de opgravingen van de norbertinessenkerk te Rekem (Belgisch Limburg) (met gegevens over laat-middeleeuwse lichaamsbalseming) - Janssens, Prud M. (Het oude land van Loon, 1979)
Keywords: rekem

The cartulary of Durford Abbey, Sussex - King, Dennis (University of Manitoba, 1979)
Keywords: durford

Der Windberger Psalter - Kirchert, Klaus (Münchener Texte und Untersuchungen zur deutschen Literatur des Mittelalters, 1979)
Keywords: windberg

Een vurige draak in Menko's Kroniek - Künzel, Rudi (Volkskundig Bulletin: Tijdschrift voor Nederlandse Cultuurwetenschap, 1979)
A fiery dragon in the chronicle of Menko.
Keywords: bloemhof

Gründung und wirtschaftliche Entwicklung des Prämonstratenserstiftes Spieskappel in Hessen - List, Gerhard (Quellen und Forschungen zur hessischen Geschichte, 1979)
Keywords: spieskappel

Leiston Abbey Cartulary and Butley Priory Charters - Mortimer, Richard C. (Suffolk Charters, 1979)
Keywords: leiston

Dragsmarks kyrka - Myrström, Linnéa (s.n., 1979)
Keywords: dragsmark

850 Jahre Reformbasilika Hane, Bolanden - Obry, Karl (Heimatverein, 1979)
Keywords: hane

Die Herren von Bolanden und ihr Hauskloster. 850 Jahre Kloster Hane (1129-1979) - Obry, Karl (Donnersberg-Jahrbuch, 1979)
Keywords: hane

Gestalterische Symbolik in der ehemaligen Abtei Rommersdorf. - Deutung abstrakter, geometrischer Sinnzeichen sowie Pflanzen und Tiersymbole - Reinhard, Hermann (Heimatjahrbuch des Landkreises Neuwied, 1979)
Keywords: rommersdorf

La mystique du sanctuaire chez Maître Adam de Dryburgh - Reuviaux, Norbert (Analecta Praemonstratensia, 1979)
Keywords: 👤 adam of dryburgh

Trudne drogi: 1126-1976 : pamiątka 850-lecia istnienia zakonu norbertańskiego - Rytko, Maria Bogumiła (Kuria Metropolitalna, 1979)
Keywords: 🇵🇱 poland (general)

Die eine Kirche, der Papst und die Konzilien in den Dialogen des Anselm von Havelberg (gest. 1158) - Sieben, Hermann Josef (Theologie und Philosophie, 1979)
Keywords: 👤 anselm of havelberg

Das Kloster Hopels im friesischen Lande Östringen - Siefken, Siefke Ortgies (Selbstverlag, 1979)
Keywords: hopels

Excavations at Whithorn Priory, 1972 and 1975 - Tabraham, Christopher J. (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1979)
Keywords: whithorn

Aus alten Chroniken und Urkunden. Unveröffentlichtes aus der Geschichte des Klosters Langwaden - Tauch, Max (Beiträge zur Geschichte der Stadt Grevenbroich, 1979)
Keywords: langwaden

Une version des statuts de Prémontré au début du XIIe siècle - Thomas, A. H. (Analecta Praemonstratensia, 1979)
Keywords: ⚖️ chapters and statutes

Acta et decreta Capitulorum Generalium Ordinis Praemonstratensis 4: 1588 - 1660 - Valvekens, Johannes B. (Abbatia Averbodiensis, 1979)
Keywords: ⚖️ chapters and statutes

De habitudine nonnullorum Praemonstratensium ad Concilium Basileense (a. 1431 ss.) notae quaedam - Valvekens, Johannes B. (Analecta Praemonstratensia, 1979)
Keywords: 📚 premonstratensian (general)

Ehemalige Klosterkirche Füssenich - heute Pfarrkirche mit Alderikus-Sarkophag - Van Der Broeck, Heribert (Jahrbuch für den Kreis Euskirchen, 1979)
Keywords: füssenich

L'abbaye de Ressons, ordre de Prémontre - Vanaertenryck, Jean (Bulletin archéologique de la région de Méru, 1979)
Keywords: ressons

Glas uit de kerk van het norbertinessenklooster te Rekem - Vanderhoeven, M. (Het oude land van Loon. Jaarboek van de Federatie der Geschied- en Oudheidkundige Kringen van Limburg, 1979)
Keywords: rekem

Barlings Abbey - White, Andrew (Lincolnshire Museums Information Sheet, Archaeology Series, 1979)
Keywords: barlings

Tupholme Abbey - White, Andrew (Lincolnshire Museums Information Sheet, Archaeology Series, 1979)
Keywords: tupholme

Geschichte des Prämonstratenserklosters Rot - Willburger, August (Rot an der Rot. Seine Geschichte und seine beiden Kirchen, 1979)
Keywords: rot an der rot

Ferrerías del Real Monasterio de Urdax - Zudaire Huarte, Eulogio (Cuadernos de Etnología y Etnografía, 1979)
Keywords: urdax

Rekonstruktion des Klosters "Unser Lieben Frauen" in Magdeburg (Architektur der DDR, 1978)
Keywords: magdeburg

Der heilige Norbert und sein Orden im Bistum Regensburg - Backmund, Norbert (Beiträge zur Geschichte des Bistums Regensburg, 1978)
Keywords: 🇩🇪 germany (general)

Evermod: erster Bischof von Ratzeburg , 17. Februar 1178 - Backmund, Norbert; Groß, Heinz-Dietrich (Verein d. Freunde d. Ratzeburger Doms, 1978)
Keywords: 👤 evermod of ratzeburg

Hermann, Prämonstratenser in Weißenau - Borst, Arno (Mönche am Bodensee, 610-1525, 1978)
Keywords: weissenau

L'abbaye de Valsery - Chauvin-Chaleil, Edith (Mémoires de la Fédération des Sociétés d'histoire et d'archéologie de l'Aisne, 1978)
Keywords: valsery

Monuments sigillographiques et héraldiques de l'ancien monastère de Fontaine-André - Clottu, Olivier (Archives héraldiques suisses = Schweizerisches Archiv für Heraldik = Archivio araldico Svizzero, 1978)
Keywords: fontaine-andré

Praemonstratensia aus Magdeburg im Kloster Strahov (Prag) - Dolista, Karel (Secundum regulam vivere : Festschrift für P. Norbert Backmund, O. Praem., 1978)
Keywords: magdeburg; strahov

Steuerlisten mecklenburgischer Bauerndörfer des 15. und 16. Jahrhunderts: Amt Gadebusch mit Kloster Rehna - Endler, Carl August (Schriften zur mecklenburgischen Geschichte, Kultur und Landeskunde, 1978)
Keywords: rehna

Der Park der Prämonstratenserabtei Rommersdorf - Engel, Doris (Rheinische Heimatpflege : Mitteilungen des Rheinischen Vereins für Denkmalpflege und Landschaftsschutz e.V. u. d. Verschönerungs-Vereins für das Siebengebirge, 1978)
Keywords: rommersdorf

Wann wurde die Kirche in Dorlar erbaut? - Ewert, Franz (Heimatkundliche Arbeitsgemeinschaft Lahntal, 1978)
Keywords: dorlar

L'Abbaye de Blanchelande: notice historique et descriptive - Fournée, Jean (Revue du Département de la Manche, 1978)
Keywords: blanchelande

Die Prämonstratenser in Köln und Dünnwald: eine Würdigung ihres Wirkens im Rahmen des Rechtsentwicklung vom hohen Mittelalter bis in die Neuzeit - Gehle, Burkhard (Kanonistische Studien und Texte, 1978)
Keywords: dünnwald

Das Kloster auf dem Beselich: Wallfahrtsort im Weilburgischen - Gelbhaar, Klaus (Heimat an Lahn und Dill, 1978)
Keywords: beselich

Le fonds des Prémontrés de Sainte-Marie-au-Bois et de Sainte-Marie Majeure aux archives de Meurthe-et-Moselle - Gérard, Pierre (Bulletin d'information des Archives Départementales de Meurthe-et-Moselle, 1978)
Keywords: sainte-marie-au-bois

Snoepende zusters te Keizerbos - Gerits, Jan (Rondom het Leudal : tijdschrift voor natuur, geschiedenis en milieu, 1978)
Keywords: keizerbosch

The Riot at Bayham Abbey, June 1525 - Goring, Jeremy (Sussex Archæological Collections, 1978)
Keywords: bayham

Een brief om inlichtingen voor de biografie van Norbertus door Ch.-L. Hugo - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1978)
Keywords: 👤 norbert of xanten

Norbertus aartsbisschop van Maagdenburg (1126-1134) - Grauwen, Wilfried Marcel (Verhandelingen van de Koninklijke Academie voor Wetenschappen, Letteren en Schone Kunsten van België, Klasse der Letteren, 1978)
Keywords: 👤 norbert of xanten

Evermod und die Anfänge des Bistums Ratzeburg - Groß, Heinz-Dietrich (Lauenburgische Heimat, 1978)
Keywords: 👤 evermod of ratzeburg

Die Ausgrabungen im ehemaligen Himmelpfortkloster - Harl, Ortolf (Jahrbuch des Vereins für Geschichte der Stadt Wien, 1978)
Keywords: himmelspforte (austria)

Der Cappenberger Barbarossakopf - Hoeps, Reinhard (Das Münster am Hellweg, 1978)
Keywords: cappenberg

Die Peterskirche von Gelnhausen: einst "Zankapfel" zwischen Bürgerschaft und Ratsherren - Hundelshausen, Lutz (Gelnhäuser Heimat-Jahrbuch, 1978)
Keywords: gelnhausen (peterskirche)

The Canons of Prémontré at the University of Ingolstadt, 1472-1550 - John, James J. (Secundum regulam vivere : Festschrift für P. Norbert Backmund, O. Praem., 1978)
Keywords: 📚 premonstratensian (general)

Expansion und Rekrutierung der Prämonstratenser 1120-1150 - Kroll, Hildegard (Analecta Praemonstratensia, 1978)
Keywords: 📚 premonstratensian (general)

Die Prämonstratenser-Pröpste des Klosters Lorsch - Kunz, Rudolf (Beiträge zur Geschichte des Klosters Lorsch, 1978)
Keywords: lorsch

L'abbaye de Moncetz - Kwanten, André (Analecta Praemonstratensia, 1978)
Keywords: moncetz

Die ehemalige Prämonstratenserabtei Rommersdorf am Mittelrhein - Lahr, Rudolf (Rheinische Heimatpflege, 1978)
Keywords: rommersdorf

L'Abbaye de Beauport (en Kérity Paimpol): ordre des prémontrés - Larivain, Henri (Les presses bretonnes, 1978)
Keywords: beauport

Les Statuts de Prémontré au milieu du XIIe siècle - Lefèvre, Placide Fernand; Grauwen, Wilfrid M. (Bibliotheca Analectorum Praemonstratensium, 1978)
Keywords: ⚖️ chapters and statutes

Das Prämonstratenserkloster Osterhofen: Seine kirchengeschichtliche und kulturelle Bedeutung für Niederbayern - Leidl, August (Festschrift zur 600jährigen Wiederkehr der Stadterhebung 1378, 1978)
Keywords: osterhofen

Vivianus von Prémontré : ein Gegner Abaelards in der Lehre von der Freiheit - Leinsle, Ulrich G. (Bibliotheca Analectorum Praemonstratensium, 1978)
Keywords: 📚 premonstratensian (general)

Dictionnaire d'histoire monastique ardennaise, Belval-en-Dieulet, abbaye de Prémontrés - Marchal, Jean (Les cahiers d'études ardennaises, 1978)
Keywords: belval

Secundum regulam vivere : Festschrift für P. Norbert Backmund, O. Praem. - Melville, Gert (Poppe-Verlag, 1978)
Keywords: 📚 premonstratensian (general)

Die Restauration der Dortfkirche Pretzien - Meussling, Maria (Standpunkt : evangelische Monatsschrift, 1978)
Keywords: leitzkau

Zur Geschichte und Baugeschichte des Klosters Jerichow - Naumann, Rolf (Kreisheimatmuseum, 1978)
Keywords: jerichow

Die skandinavische Zirkarie der Premonstratenserchorherren - Nyberg, Tore (Secundum Regulam Vivere: Festschrift für P. Norbert Backmund, O. Praem, 1978)
Keywords: 🇩🇰 denmark (general); 🇳🇴 norway (general); 🇸🇪 sweden (general)

Das Prämonstratenserstift Osterhofen und die Herren von Chambe-Hals - Oswald, Josef (Secundum regulam vivere. Festschrift für P. Norbert Backmund O.Praem., 1978)
Keywords: osterhofen

L’église abbatiale d’après l’ordinaire de Prémontré - Petit, François (Actes officiels du IVe colloque du Centre d’études et recherches Prémontrées, 1978)
Keywords: 📚 premonstratensian (general)

Geras-Pernegg und die Babenberger - Pfiffig, Ambros Josef (Secundum regulam vivere. Festschrift für P. Norbert Backmund O.Praem., 1978)
Keywords: geras; pernegg

Dzieje i fabryka kościoła oraz klasztoru Norbertanek w Imbramowicach - Pieńkowska, Hanna (Folia Historiae Artium, 1978)
L'histoire et la fabrique de l'église et du couvent prémontrées d'Imbramowice.
Keywords: imbramowice

L’art chez les Prémontrés à travers la collection de carreaux de pavage découverts à l’abbaye de Dommartin (Saint - Josse - au - Bois), Pas-de-Calais - Pontroue, Pierre (Analecta Praemonstratensia, 1978)
Keywords: dommartin

Die Genealogie der Welfen in einer bayerischen Klosterkirche. Steingaden (Obb.). - Remmler, Karl (Unser Harz, 1978)
Keywords: steingaden

Adam de Dryburgh et la spiritualité prémontrée au XIIe siècle - Reuviaux, Norbert (Actes officiels du 3ème colloque du Centre d'études et de recherches prémontrée, 1978)
Keywords: 👤 adam of dryburgh

Gebhard, Propst und erster Abt von Windberg. Skizzen zur Frühgeschichte einer Prämonstratenser-Abtei - Rommens, Rainer (Secundum regulam vivere. Festschrift für P. Norbert Backmund O.Praem., 1978)
Keywords: windberg

Das Kloster Barthe - Saathoff, Johann (Unser Ostfriesland, 1978)
Keywords: barthe

Die Prämonstratenser-Abtei Hamborn in Duisburg - Scheiermann, Friedrich (Rheinische Kunststätten, 1978)
Keywords: hamborn

De abten van Grimbergen voor de Franse Revolutie, 1128-1794 - Spillemaeckers, C. L (Abdijboekhandel, 1978)
Keywords: grimbergen

Rot an der Rot: (Mönchsroth) ; ehem. Prämonstratenser-Reichsabtei, Kreis Biberach, Riss, Baden-Württemberg - Stemmer, Walter; Schnell, Hugo (Kleine Kunstführer, 1978)
Keywords: rot an der rot

Die Pfarreien des Prämonstratenserstifts Adelberg - Tüchle, Hermann (Secundum regulam vivere. Festschrift für P. Norbert Backmund O.Praem., 1978)
Keywords: adelberg

L'abbaye Notre-Dame de Lieu-Restauré (Oise) - Valvekens, Johannes B. (Analecta Praemonstratensia, 1978)
Keywords: lieu-restauré

Miscellanea 2. L'abbaye de Fontcaude - Valvekens, Johannes B. (Analecta Praemonstratensia, 1978)
Keywords: fontcaude

Miscellanea 6. L'art chez les Prémontrés à travers la collection de carreaux de pavage découverts à l'abbaye de Dommartin = Saint-Josse-au-Bois - Valvekens, Johannes B. (Analecta Praemonstratensia, 1978)
Keywords: dommartin

Het voormalige klooster Mariëngaarde bij Hallum - Van den Berg, Herma M. (Publicaties Stichting Alde Fryske Tsjerken, 1978)
Keywords: mariëngaarde

Het archief van de abdij van Postel - Vanhoof, Franciscus (Archives et bibliothèques de Belgique, 1978)
Keywords: postel

Rommersdorf und das "Koblenzer Land". Die Ausstrahlungskraft der alten Prämonstratenser-Abtei. - Winnen, August Peter (Heimatjahrbuch des Landkreises Neuwied, 1978)
Keywords: rommersdorf

Klooster Lidlum bij Oosterbierum was eens centrum van economie en cultuur in Noordwest-Friestland - Meijer, T.W. (Nederlands Dagblad, 1977)
Keywords: lidlum

Het Premonstratenzer vrouwenklooster te Keizerbos Neer - Gerits, Jan (Rondom het Leudal : tijdschrift voor natuur, geschiedenis en milieu, 1977)
Keywords: keizerbosch

Dzieje klasztoru PP. Norbertanek w Krakowie na Zwierzyńcu do roku 1840, cz.I, - Kramarska-Anyszek, Krystyna (Nasza Przeszłość, 1977)
The article presents the history of the Norbertine convent in Krakow, Zwierzyniec, until 1840. It begins with a description of the foundation and organisation of the new monastery, as well as a description of Blessed Bronisława's stay in the Order and everyday life in the monastery. The development of the monastery in the following centuries is then shown through the characteristics of the individual abbesses. The study tries to include important events such as the restoration of the church, renovations, the expansion of the convent and the improvement of the nuns' living conditions. Finally, educational initiatives such as the parish school are discussed, as well as examples of the generosity and commitment to the life of the order of various people who collaborated with the Swierzyniec convent.
Keywords: zwierzyniec

Bokenäs gamla kyrka : en kort information (1977)
Keywords: bokenäs

Kloster Adelberg: Landkreis Göppingen, Dekanat Schorndorf - Akermann, Manfred; Ziegler, Walter (Kleine Kunstführer, 1977)
Keywords: adelberg

Cappenberg. Stiftskirche – Schloß – Museum - Appuhn, Horst (Große Baudenkmäler, 1977)
Keywords: cappenberg

L'Abbaye Notre Dame de Jandeures (Jeand'heurs) - Arnod, Michel; Demandre, Jean Luc (Syndicat d'initiative, 1977)
Keywords: jandeures

Kloster Windberg: Studien zu seiner Geschichte - Backmund, Norbert (Poppe Verlag, 1977)
Keywords: windberg

La division de l'ordre de Prémontré en circaries : nouveaux aspects - Backmund, Norbert (Actes officiels du IIIe colloque du Centre d'Etudes et de Recherches Prémontrées, 1977)
Keywords: 📚 premonstratensian (general)

Ordo Praemonstratensis in Italia. Circariae Tusciae et Calabriae - Backmund, Norbert (Brundisii res, 1977)
Keywords: 🇮🇹 italy (general)

Rarissimo ritratto premonstratense nello spoletino - Backmund, Norbert (Spoletium. Rivista di arte storia cultura, 1977)
Keywords: 🇮🇹 italy (general)

Le Patrimoine de l'Abbaye Saint-Jean de Falaise: ordre de Prémontrés - Bled, Isabelle (Université de Caen Normandie, 1977)
Keywords: falaise

Letzte Spuren der Bibliothek des Klosters Elsey - Bleicher, Wilhelm (Heimatblätter für Hohenlimburg und Umgebung, 1977)

Les abbés et les prévôts commémorés à Sainte-Marie-au-Bois - Brouette, Émile (Analecta Praemonstratensia, 1977)
Keywords: sainte-marie-au-bois

Das ehemalige Prämonstratenserinnen-Kloster Wenau in Langerwehe bei Düren - Candels, Heinrich (Rheinische Kunststätten, 1977)
Keywords: wenau

The life of St. Norbert by John Capgrave, O.E.S.A.: 1393 - 1464 - Capgrave, John (Studies and texts, 1977)
Keywords: 👤 john capgrave; 👤 norbert of xanten

Historia de Santa Maria de Bellpuig de las Avellanas - Caresmar, Jaime (1977)
Keywords: bellpuig de las avellanes

Cappel, das westfälische Kulturkleinod – eine Kirchen- und Klostergründung des Prämonstratenserordens in der bedeutsamen Stauferzeit des 12. Jahrhunderts - Eickhoff, Paul (P. Eickhoff, 1977)
Keywords: cappel

Anselm of Canterbury and Anselm of Havelberg: the controversy with the Greeks - Evans, Gillian Rosemary (Analecta Praemonstratensia, 1977)
Keywords: 👤 anselm of havelberg

Wederwaardigheden rond de reformatie van het Witvrouwenklooster te Keizerbos - Genechten, Vincenz van (Analecta Praemonstratensia, 1977)
Keywords: keizerbosch

El monasterio premonstratense de Urdax et la Edad Media (1182-1520) - Goñi Gaztambide, José (Homenaje a Fray Justo Pérez de Urbel, O.S.B, 1977)
Keywords: urdax

De geschiedenis van Gennep en de afstamming van Norbertus - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1977)
Keywords: 👤 norbert of xanten

De Norbertusbiografie in de geschiedenis van het aartsbisdom Maagdenburg - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1977)
Keywords: magdeburg; 👤 norbert of xanten

Gertrud von Altenberg: vor 750 Jahren geboren. Die Tochter d. heiligen Elisabeth. Ein Leben in Demut u. Dienstbarkeit - Hinze, Kurt (Heimat an Lahn und Dill, 1977)
Keywords: altenberg

Stift Elsey und seine räumliche Verflechtung im südlichen Westfalen - Klueting, Edeltraud (Westfälische Zeitschrift: Zeitschrift für vaterländische Geschichte und Altertumskunde, 1977)
Keywords: elsey

La messe matinale dans l'ordre de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1977)
Keywords: 🛐 liturgy

La messe matinale dans la liturgie de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1977)
Keywords: 🛐 liturgy

Quatre services annuels pour tous les défunts dans l'ordre de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1977)
Keywords: 🛐 liturgy

An Edition of the Cartulary of Leiston Abbey - Mortimer, Richard C. (King's College London, 1977)
Keywords: leiston

Weißenauer Chronik des Bauernkrieges von 1525 - Murer, Jakob (Thorbecke, 1977)
Keywords: weissenau

Kloster Schäftersheim. Baugeschichtliche Untersuchungen über das ehemalige Prämonstratenserinnenkloster Schäftersheim bis zu seinem Niedergang im 16. Jahrhundert - Sauer, Karl-Ernst (Württembergisch Franken, 1977)
Keywords: schäftersheim

Torre Abbey: an account of its history, buildings, cartularies and lands. - Seymour, Deryck (James Townsend, 1977)
Keywords: torre

Juwel der Baukunst. Abtei Rommersdorf in der Obhut einer Stiftung. - Stelz, Fritz (Heimatjahrbuch des Landkreises Neuwied, 1977)
Keywords: rommersdorf

Dem Vorbild der seligen Gertrud verpflichtet: Altenberg an d. Lahn. Aus Vergangenheit u. Gegenwart eines ehemaligen Klosters - Stenger, Hans Ulrich (Almanach. Jahrbuch für das Bistum Limburg, 1977)
Keywords: altenberg

L'abbaye de Mondaye - Vanuxem, Jacques (Annales de Normandie, 1977)
Keywords: mondaye

Les chapiteaux du cloître de l'abbaye de Fontcaude - Vignes-Dumas, Claire (Bulletin Monumental, 1977)
Keywords: fontcaude

A propos des Instructions pour les clercs (De Institutione clericorum) de Philippe de Harveng - Weyns, Norbert J. (Analecta Praemonstratensia, 1977)
Keywords: 👤 philip of harvengt

Die Waldungen des Klosters Rüti : ein Beitrag zur zürcherischen Forstgeschichte - Witschi, Peter (University of Zürich, 1977)
Keywords: rüti

Rękopisy liturgiczne biblioteki pp. Norbertanek w Imbramowicach - Nir, Roman (Ruch Biblijny i Liturgiczny, 1976)
Keywords: imbramowice

De molen van Sint-Antelinks gevallen (De Belgische Molenaar, 1976)
Keywords: molen ter rijst

Die letzten Spuren des Klosters Hopels - Ahlrichs, Richard (Harlinger Heimatkalender, 1976)
Keywords: hopels

Aus den Ausgabenbüchern des Klosters Speinshart - Backmund, Norbert (Archiv für die Geschichte von Oberfranken, 1976)
Keywords: speinshart

Early Premonstratensian Eschatology: The Apocalyptic Myth - Bischoff, Guntram (The Spirituality of Western Christendom, 1976)
Keywords: 📚 premonstratensian (general)

Einst dem heiligen Sebastian geweiht. Kirche, Kloster und Stift zu Elsey - Bleicher, Wilhelm (Hagener Heimatkalender, 1976)
Keywords: elsey

Huize 'Den Bellaert' - Cauwenbergh, George Van; Rottiers, Jef; Willekens, Emiel (De Crans, 1976)
Keywords: den bellaert

Essai archeologique de datation des batiments de l'abbaye de Lieu-Restaure - François, Jean-Luc; Perrin, Ginette (Cahiers archéologiques de Picardie, 1976)
Keywords: lieu-restauré

Kloster Maria-Engelport bei Treis an der Mosel - Friderichs, Alfons (Rheinische Kunststätten, 1976)
Keywords: engelport

Prieuré de Rekem - Grauwen, M. (Monasticon Belge, 1976)
Keywords: rekem

Een verhandeling over de vroegste geschiedenis van Cappenberg - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1976)
Keywords: cappenberg

Was de inquisiteur Koenraad van Marburg (1233) een premonstratenzer? - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1976)
Keywords: 📚 premonstratensian (general)

Die Werkstattbeziehungen der romanischen Kirche am Zsámbék - Guzsik, Tamás (Alba Regia, 1976)
Keywords: zsámbék

Corhampton Church, Hampshire - Hurst, John (Corhampton Church, 1976)
Keywords: corhampton

Klosterherrschaft und Untertanen des Prämonstratenser Chorfrauenstiftes Chotieschau - Hüttl, Josef (Analecta Praemonstratensia, 1976)
Keywords: chotěšov

Biedenkopf und Nonnenkloster Keppel bei Hilchenbach - Immel, Otto (Hinterländer Geschichtsblätter, 1976)
Keywords: keppel

Urkundenbuch der Abtei Steinfeld - Joester, Ingrid (Publikationen der Gesellschaft für Rheinische Geschichtskunde, 1976)
Keywords: steinfeld

Das Elseyer Registrum mortuorum Fabiani et Sebastiani - Klueting, Edeltraud (Heimatblätter für Hohenlimburg und Umgebung, 1976)

Zur Geschichte des Stiftes Elsey - Klueting, Edeltraud (Heimatblätter für Hohenlimburg und Umgebung, 1976)
Keywords: elsey

Abdijbezit van Tongerlo te Turnhout - Koyen, Milo Hendrik (Taxandria, 1976)
Keywords: tongerlo

Zur Echtheitsfrage der sogenannten Cappenberger Gründungsurkunde von 1122 - Kracht, August (Der Märker. Landeskundliche Zeitschrift für den Bereich der ehem. Grafschaft Mark und den Märkischen Kreis, 1976)
Keywords: cappenberg

Le problème des soeurs aux origines de l'abbaye d'Averbode - Lefèvre, Placide (Analecta Praemonstratensia, 1976)
Keywords: averbode

Het vertrek van Sint-Catharinadal naar Oosterhout en wat daaraan vooraf ging - Lepper, Johannes L. M. de (Jaarboek van de geschieden oudheidkundige Kring van stad en land van Breda "De Oranjeboo", 1976)
Keywords: sint-catharinadal

Die Bibliothek des Prämonstratenser-Reichsstiftes Ursberg 1125 bis 1803 - Lohmüller, Alfred (Jahrbuch des Vereins für Augsburger Bistumsgeschichte, 1976)
Keywords: ursberg

L'abbaye de Floreffe - Lombet, Jean (Wallonie, art et histoire, 1976)
Keywords: floreffe

Einstige Lettner in den Kirchen der Doppelklöster Enkenbach und Kaiserslautern - Lutz, Karl (Jahrbuch zur Geschichte von Stadt und Landkreis Kaiserslautern, 1976)
Keywords: enkenbach

Colección diplomática burgalesa. I. Diplomatario de San Cristóbal de Ibeas - Martínez, Gonzalo (Boletín de la Institución Fernán González, 1976)
Keywords: ibeas

Das Prämonstratenserstift Schlägl - Reischl, Friedrich; Pichler, Isfried Hermann (Oberösterreichische Kulturberichte, 1976)
Keywords: schlägl

Die ehemalige Prämonstratenser Klosterkirche St. Maria und Michael in Churwalden - Rutishauser, Hans (University of Zürich, 1976)
Keywords: churwalden

Dictionnaire historique des communes des Ardennes: Septfontaines-en-Thiérache - Sery, Jean (Revue historique ardennaise, 1976)
Keywords: septfontaines en thiérache

Sint-Antelinks. Molen ter Rijst - Smet, L. (Molenecho's, 1976)
Keywords: molen ter rijst

850 Jahre Rot an der Rot. Geschichte und Gestalt. Neue Beiträge zur Kirchen- und Kunstgeschichte der Prämonstratenser-Reichsabtei - Tüchle, Hermann; Schahl, Adolf (J. Thorbecke, 1976)
Keywords: rot an der rot

L'abbaye de Fontcaude. Étude historique - Vignes, Claire (Analecta Praemonstratensia, 1976)
Keywords: fontcaude

The Hagnaby Chronicle and the battle of Maes Moydog - Walker, R. F. (Welsh History Review, 1976)
Keywords: hagnaby

Tommarps urkundsbok: klostret - hospitalet - staden - socknen: 1300-1450 - Wallin, Curt (Verbum, 1976)
Keywords: tommarp

Kloster Rommersdorf - Winnen, August Peter (Landeskundliche Vierteljahrsblätter, 1976)
Keywords: rommersdorf

Rommersdorf und Sayn. Die gutnachbarlichen Beziehungen zweier Prämonstratenser-Abteien. - Winnen, August Peter (Heimatjahrbuch des Landkreises Neuwied, 1976)
Keywords: rommersdorf; sayn

Das Kloster Speinshart im Mittelalter - Backmund, Norbert (Analecta Praemonstratensia, 1975)
Keywords: speinshart

Diversas formas de actividad y trabajo en el Prémontré - Backmund, Norbert (Yermo: Cuadernos de historia y de espiritualidad monasticas, 1975)
Keywords: 📚 premonstratensian (general)

Ein Profeßbuch des Klosters Speinshart - Backmund, Norbert (Ostbairische Grenzmarken, 1975)
Keywords: speinshart

Die Anbetung der Heiligen Drei Könige aus der Klosterkirche Altenberg bei Wetzlar - Bauer, Walter (Heimatblätter zur Pflege und Förderung des Heimatgedankens, Beilage zur Dill-Zeitung, 1975)
Keywords: altenberg

De collectie ikonen van de Abdij van Berne - Bavel, Huub van (Analecta Praemonstratensia, 1975)
Keywords: berne

Die Stifterfenster der Wallfahrtskirche zu Lautenbach - Becksmann, Rüdiger (Vitrea dedicata: das Stifterbild in der deutschen Glasmalerei des Mittelalters, 1975)
Keywords: lautenbach

Das Prämonstratenserinnenstift Wenau: Conventus Sancte Katerine de Wenowe - Candels, Heinrich (Veröffentlichungen des Bischöflichen Diözesanarchivs Aachen, 1975)
Keywords: wenau

Die Schriftbänder in den Wand- und Gewölbebildern im Kreuzgang des ehemaligen Prämonstratenserklosters Wedinghausen (Arnsberg) - Claussen, Hilde; Eickermann, Norbert (Westfalen. Hefte für Geschichte, Kunst und Volkskunde, 1975)
Keywords: wedinghausen

L'abbaye de Belval (Ardennes) au XIIe siècle et son cartulaire inédit - Collin, Hubert (Actes du 98e Congrès National des Sociétés Savantes, Saint-Etienne, 1973. Section de philologie et d'histoire jusqu'à 1610: Forez et Velay, questions d'histoire et de philologie, 1975)
Keywords: belval

Les richesses de la terre: Cîteaux et Prémontré devant l'économie de profit aux XIIe et XIIIe siècles - Despy, Georges (Problèmes d'histoire du christianisme, 1975)
Keywords: 📚 premonstratensian (general)

Acta capitulorum triennalium et annalium circariae Saxoniae ordinis Praemonstratensis inde ab anno 1466 usque ad annum 1516 - Dolista, Karel (Analecta Praemonstratensia Editiones textuum, 1975)
Keywords: ⚖️ chapters and statutes

Klášterní hrad v Dolních Kounicích - Eliáš, Jan O.; Kašička, František (Zprávy památkové péče, 1975)
Le château-monastère à Dolní Kounice.
Keywords: kounice

L'abbaye de Belle-Étoile. 1: L'abbaye à travers les siècles - Fournée, Jean (Le pays bas-normand, 1975)
Keywords: belle-étoile

De Maagdeburgse kapittels in de Germania Sacra - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1975)
Keywords: magdeburg

Lijst van oorkonden waarin Norbertus wordt genoemd - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1975)
Keywords: 👤 norbert of xanten

Norbert et les débuts de l'abbaye de Floreffe - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1975)
Keywords: floreffe; 👤 norbert of xanten

Reepsholt und Hopels, ehemalige Klöster in Ostfriesland. - Heckmann, Erich (Leuchtfeuer, 1975)
Keywords: hopels

Les types d’exploitations cisterciennes et prémontrées du XIIIe siècle et leur rôle dans la formation de l’habitat et des paysages ruraux - Higounet, Charles (Paysages et villages neufs du Moyen Age : recueil d'articles de Charles Higounet, 1975)
Keywords: 📚 premonstratensian (general)

Bruchstück von einem Nekrolog des Prämonstratenserstiftes Hamborn - Horstkötter, Ludger (Annalen des Historischen Vereins für den Niederrhein, 1975)
Keywords: hamborn

Die Abteikirche in Hamborn. Theologische und geschichtliche Anregungen - Horstkötter, Ludger (Braun, 1975)
Keywords: hamborn

Les sceaux de l'abbaye et des abbes de Floreffe - Houtman, Erik (Miscellanea archivistica, 1975)
Keywords: floreffe

La fête de la Trinité chez les prémontrés et dans la tradition canoniale - Lefèvre, Placide (Analecta Praemonstratensia, 1975)
Keywords: 🛐 liturgy

Le Saint-Augustin et la concurrence de la Décollation de saint Jean-Baptiste dans la liturgie de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1975)
Keywords: 🛐 liturgy

Ein mittelalterliches Glasgemälde aus der Prämonstratenserabtei zu Bendorf-Sayn - Liessem, Udo (Jahrbuch der Stadt Bendorf am Rhein, 1975)
Keywords: sayn

Colección diplomática burgalesa. I. Diplomatario de San Cristóbal de Ibeas - Martínez, Gonzalo (Boletín de la Institución Fernán González, 1975)
Keywords: ibeas

House of Premonstratensian canons: Abbey of Leiston - Page, William (A History of the County of Suffolk, 1975)
Keywords: leiston

L'abbaye de Doue - Saint-Jean, Robert (Congrès archéologique de France : séances générales, 1975)
Keywords: doue

Rätsel um Figuren und Wappen am Cappeler Stift gelöst - Schmieder, Siegfried (Heimatblätter Lippstadt, 1975)
Keywords: cappel

Eine Sakristei des 13. Jahrhunderts in der Kirche des ehemaligen Prämonstratenserinnenklosters zu Oelinghausen, Kreis Arnsberg - Schwedhelm, Sabine (Westfalen. Hefte für Geschichte, Kunst und Volkskunde, 1975)
Keywords: oelinghausen

Excavations at Cockersand Abbey, Lancashire, 1923-27 - Sherdley, Hugh; White, A. J. (Contrebis: a bulletin of archaeology for Lancashire and the North West, 1975)
Keywords: cockersand

Sint-Antelinks. Molen ter Rijst - Smet, L. (Molenecho's, 1975)
Keywords: molen ter rijst

Kirche Damenstift Osterhofen-Altenmarkt: ehem. Prämonstratenserabteikirche Osterhofen, heute Pfarrkirche Altenmarkt - Stadlthanner, Helmut (Kleine Kunstführer, 1975)
Keywords: osterhofen

Überblick über die Geschichte von Pfarre, Kloster und Kirche St. Nikolaus Dünnwald - Stanzel, J. (Die Bürgermeisterei Merheim im Wandel der Zeit, 1975)
Keywords: dünnwald

Bény - a volt premontrei templom - Taliga, István (Irodalmi Szemle, 1975)
Keywords: bíňa

Stichting en status van het Wittevrouwenklooster te Utrecht - Van Campen, J.W.C. (Archief voor de geschiedenis van de Katholieke Kerk in Nederland, 1975)
Keywords: wittevrouwen

De munten en de penningen opgegraven in de gewezen Abdij van Dieleghem - Vanderpijpen, Willy (Comté de Jette. Annales, 1975)
Keywords: dieleghem

Beauchief Abbey Past and Present - Walton, M.; Meredith, R. (Local studies leaflets, 1975)
Keywords: beauchief

Inventaire des archives de l'abbaye de Saint-Feuillien du Rœulx - Wymans, Gabriel (Archives Générales du Royaume, 1975)
Keywords: rœulx

Trois documents inédits sur l'abbaye de Blanchelande - Demouy, Patrick (Revue du Département de la Manche, 1974)
Keywords: blanchelande

Plan of St Nicholas Church Oxney drawn 16 June 1974 (St Margaret's Village History, 1974)
Keywords: oxney

Friedrich von Hallum - Backmund, Norbert (Lexikon der christlichen Ikonographie, 1974)
Keywords: mariëngaarde

Gilbert von Neuffontaines - Backmund, Norbert (Lexikon der christlichen Ikonographie, 1974)
Keywords: neuffontaines

Le diocèse de Bourges et l'ordre de Prémontré - Bigonneau, Hugues (La Vie catholique du Berry, 1974)
Keywords: 🇫🇷 france (general)

Evermod von Ratzeburg - Boberg, Jochen (Lexikon der christlichen Ikonographie, 1974)
Keywords: 👤 evermod of ratzeburg

De abdij van Tongerlo en de zielzorg in Roosendaal - Dekkers, W. C. A. (Jaarboek van de Oudheidkundige Kring De Ghulden Roos Roosendaal, 1974)
Keywords: tongerlo

Le monastère de Château-l'Abbaye, des origines à 1314 - Desreumaux, Roger (Bulletin de la Commission Historique du Département du Nord, 1974)
Keywords: château-l'abbaye

Norbert van Gennep en de "Orde canonicus". Evangelisch leven tussen restauratie en vernieuwing - Dijck, L. van C. (Ons geestelijk erf, 1974)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Die Triennal- und Annual kapitel der sächsischen Zirkarie des Prämonstratenserordens: Eine Einleitung zur beabsichtigten Edition Acta capitulorum triennalium et annalium circariae Saxoniae ordinis Praemonstratensis inde ab anno 1466 usque ad annum 1516 - Dolista, Karel (Analecta Praemonstratensia, 1974)
Keywords: ⚖️ chapters and statutes; 🇩🇪 germany (general)

Graduál z kláštera řádu premonstrátů v Louce u Znojma - Eidernová-Pštrossová, Vladimíra (Charles University, 1974)
Keywords: louka

John Capgrave's first English composition, "The Life of St. Norbert" - Fredeman, Jane Cowan (Bulletin of the John Rylands Library, 1974)
Keywords: 👤 john capgrave; 👤 norbert of xanten

Kilmore Diocese and the Premonstratensian Order - Gallogly, Daniel (1924-1974: Golden Jubilee Souvenir of Holy Trinity Abbey, Kilnacrott, Ireland, 1974)
Keywords: 🇮🇪 ireland (general)

Boekenbezit en boekengebruik in de middeleeuwse Premonstratenzerabdijen van de Nederlanden - Gerits, Trudo (Contributions à l'histoire des bibliothèques et de la lecture aux Pays Bas avant 1600 / Studies over het boekenbezit en boekengebruik in de Nederlanden vóór 1600, 1974)
Keywords: 🇳🇱 netherlands (general)

Die Wadgasser Prämonstratenser im Köllertal - Gillet, Josef (Köllertaler Heimatbuch : Landschaft, Geschichte u. Volkskunde d. mittleren Köllertales, 1974)
Keywords: wadgassen

Was Norbertus tevens kanunnik van Sint-Servaas te Maastricht? - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1974)
Keywords: 👤 norbert of xanten

Adam of Dryburgh: Six Christmas Sermons - Hamilton, M.J. (Analecta Cartusiana, 1974)
Keywords: 👤 adam of dryburgh

The parish church of St. Peter, Titchfield, Fareham - Hare, Michael (Church Publishers, 1974)
Keywords: titchfield (st peter's)

A nyíradonyi premontrei prépostság 1936-ban feltárt maradványai - Kozák, Károly (Debreceni Déri Múzeum Évkönyve, 1974)
Keywords: nyíradony

Zur Ordenszugehörigkeit des Klosters Brunnenburg a. d. Lahn - Krings, Bruno (Nassauische Annalen, 1974)
Keywords: brunnenburg

Kopiarz opactwa Norbertanów w Nowym Sączu - Kumor, Bolesław (Studia historyczne, 1974)
The copybook of the Norbertine Abbey in Nowy Sącz
Keywords: nowy sącz

Sauvetage d'objets précieux par l'abbaye d'Averbode depuis le XVe jusqu'au XVIIIe siècle - Lefèvre, Placide (Arca Lovaniensis, 1974)
Keywords: averbode

Ursberg - Lohmüller, Alfred (Das Bayerland, 1974)
Keywords: ursberg

Histoire de l'abbaye de Lieu-Restauré - Moreau-Néret, André (Société historique régionale de Villers-Cotterets, 1974)
Keywords: lieu-restauré

Premonstratensian houses: Abbey of Coverham - Page, William (A History of the County of York, 1974)
Keywords: coverham

Premonstratensian houses: Abbey of St Agatha, Easby - Page, William (A History of the County of York, 1974)
Keywords: easby

Premonstratensian houses: Egglestone Abbey - Page, William (A History of the County of York, 1974)
Keywords: egglestone

Santa María del Tejo. Una fundación premostratense en las Asturias de Santillana - Pedraja y Gonzalez del Tanago, J. M. de la (Altamira, 1974)
Keywords: el tejo

L'Abbaye prémontrée de Corneux : XIIe-XIIIe siècles - Pheulpin, Pierre (Université de Franche-Comté, 1974)
Keywords: corneux

Abbaye de Saint-Josse-au-Bois (Dommartin). Les carreaux de pavage du Moyen Age découverts au cours des fouilles archéologiques, 1969-1974 - Pontroue, Pierre (Bulletin de la Société des Antiquaires de Picardie, 1974)
Keywords: dommartin

The Carmarthenshire possessions of Tallyllychau - Richards, Melville (Carmarthenshire Studies: Essays presented to Major Francis Jones, 1974)
Keywords: talley

Die Erbhofkaplanswürde des Abtes von Wilten vornehmlich im Mittelalter und in der frühen Neuzeit - Steinegger, Fritz (Festschrift Nikolaus Grass: zum 60. Geburtstag dargebracht von Fachgenossen, Freunden und Schülern, 1974)
Keywords: wilten

Un dels llinatges fundadors del monastir de Santa Maria de Bellpuig de les Avellanes - Tamarit i Culleres, Francesc (Ilerda / Humanitats, 1974)
Keywords: bellpuig de las avellanes

A jánoshidai rk. templom, volt premontrei prépostság régészeti kutatása (1970-1974) - Tóth, János (Jubileumi évkönyv a Jász Múzeum alapításának 100. évfordulójára, 1974)
Keywords: jánoshida

Die Orgel in der Kirche des Prämonstratenserklosters Cappel, - Trinkaus, Eckhard (Hessische Heimat, 1974)
Keywords: cappel

A propos de quelques manuscrits de l'abbaye de Parc conservés à la Bibliothèque de l'Université de Gand. - Van Acker, Kamiel G. (Archives et bibliothèques de Belgique / Archief- en bibliotheekwezen in België, 1974)
Keywords: park

Les critères de provenance des manuscrits de Parc - Van Balberghe, Emile (Contributions à l'histoire des bibliothèques et de la lecture aux Pays-Bas avant 1600: Studies over het Boekenbezit en Boekengebruik in de Nederlanden vóór 1600, 1974)
Keywords: park

Romanische Prämonstratenserinnenkirchen am Niederrhein - Verbeek, Albert (Festschrift für Franz Graf Wolff Metternich, 1974)
Keywords: 🇩🇪 germany (general)

Scheda - was wurde aus dem Kloster - Wermelskirchen, Karl-Heinz (Heimatkalender des Kreises Soest, 1974)
Keywords: scheda

Die ältesten Urkunden und die frühe Geschichte des Prämonstratenserstiftes Cappenberg in Westfalen (1122-1200). Zweiter Teil. Studien zur Geschichte Cappenbergs im 12. Jahrhundert - Petry, Manfred (Archiv für Diplomatik, 1973)
Keywords: cappenberg

Dryburgh Abbey and Bozeat, Northants - Stringer, Keith J. (The Innes Review, 1973)
Keywords: dryburgh

Abdij van Berne Heeswijk: Nederlands oudste kloostergemeenschap - Bavel, Huub van; Hurk, W. van de (Abdij van Berne, 1973)
Keywords: berne

La reconstitution du tympan de l'église Saint-Yved de Braine - Berry, Maurice (Bulletin de la Société nationale des antiquaires de France, 1973)
Keywords: braine

Wirtschafts- und Besitzgeschichte des Prämonstratenserinnen- klosters Niederilbenstadt in der Wetterau - Biedert, Hans-Karl (Quellen und Forschungen zur hessischen Geschichte, 1973)
Keywords: niederilbenstadt

Fragments de l'obituaire de Cuissy - Brouette, Émile (Analecta Praemonstratensia, 1973)
Keywords: cuissy

L'abbaye Notre-Dame d'Huveaune - Dailliez, Laurent (Marseille: Revue municipale, 1973)
Keywords: huveaune

Cockersand Abbey - Dalton, Kate (Dalton Genealogical Society Journal, 1973)
Keywords: cockersand

De proosdij Beauregard aan de Waaienburg - De Schrevel, A. (De IJzerbode, 1973)
Keywords: proven

900 Jahre Stiftskirche in Stoppenberg - Ettl, Elisabeth (Die Heimatstadt Essen, 1973)
Keywords: stoppenberg

Colección diplomática del monasterio de San Pelayo de Cerrato - Fernández Martín, Luis (Hispania sacra. Revista española de historia eclesiástica, 1973)
Keywords: san pelayo de cerrato

Un manuscrit universitaire padouan à l'abbaye de Parc - Fransen, Gérard (Mélanges offerts à Pierre Andrieu Guitrancourt, 1973)
Keywords: park

Entwicklung der Kirchenmusik und des Orgelbaues im Prämonstratenserstift Schlägl von der Gründung (1218) bis 1665, dem Todesjahr des Abtes Martin Greysing: Beiträge zu einer Musikgeschichte des Prämonstratenserstiftes Schlägl im Oberen Mühlviertel - Frieberger, Rupert Gottfried (Miscellanea aus dem Kirchenhistorischen Institut der Katholisch-Theologischen Fakultät Wien, 1973)
Keywords: schlägl; 🎶 musicology

Les Constructions médiévales de l'ancienne abbaye de Floreffe - Genicot, Luc-Francis (Centre d'histoire de l'architecture et du bâtiment, 1973)
Keywords: floreffe

Abdijen en landbouw. Cisterciënzers en Premonstratenzers in de Zuidelijke Nederlanden - Gerits, Trudo (Ons heem, 1973)
Keywords: 🇳🇱 netherlands (general)

De hoeven van de kempische Witherenabdijen - Gerits, Trudo (Ons heem, 1973)
Keywords: 🇳🇱 netherlands (general)

Historische schoonheid van Averbode: tentoonstelling in de Abdij van Averbode, 1 juli-26 augustus 1973 - Gerits, Trudo (Abdij der Norbertijnen, 1973)
Keywords: averbode

Twee bouwkontrakten voor graanschuren van Averbode en Tongerlo in de 16de eeuw - Gerits, Trudo (Ons heem, 1973)
Keywords: averbode; tongerlo

Die Geschichte des Klosters Himmelspforte in Wyhlen - Gerspach, Hansjörg (Markgräflerland : Beiträge zu seiner Geschichte und Kultur. Sonderh., 1973)
Keywords: himmelspforte (germany)

De geschiedenis van het aartsbisdom Maagdenburg tot de 12de eeuw - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1973)
Keywords: magdeburg

De sterfdatum van Norbertus' voorganger te Maagdenburg - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1973)
Keywords: magdeburg

Necrologia en obituaria - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1973)
Keywords: 📚 premonstratensian (general)

A premontreiek építkezései Győr-Sopron megyében a XII - XIII. században - Kozák, Károly (Arrabona, 1973)
Keywords: 🇭🇺 hungary (general)

Le temporel de l'abbaye de Dommartin d'aprés un censier de 1252 - Larzet, Denis (Université de Lille III, 1973)
Keywords: dommartin

Averbode et ses trésors - Lefèvre, Placide (Analecta Praemonstratensia, 1973)
Keywords: averbode

Le Saint-Laurent dans la liturgie de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1973)
Keywords: 🛐 liturgy

Het landbouwdomein van de abdij van Park-Heverlee - Maes, S. F.; Gerits, Trudo (Ons heem, 1973)
Keywords: park

L'abbaye de Chambrefontaine aux XIVe et XVe siècles - Moreau, Jean-Paul (Bulletin de la Société historique et archéologique de Goële, 1973)
Keywords: chambrefontaine

Houses of Premonstratensian canons: Abbey of Bayham - Page, William (A History of the County of Sussex, 1973)
Keywords: bayham

Houses of Premonstratensian canons: Abbey of Dureford - Page, William (A History of the County of Sussex, 1973)
Keywords: durford

Houses of Premonstratensian canons: Abbey of Otham - Page, William (A History of the County of Sussex, 1973)
Keywords: otteham

Pfarrkirche Rohrbach. Kleiner Führer durch die Pfarrkirche mit geschichtlichen Notizen zur Entstehung des Marktes u. d. Pfarre Rohrbach (Pfarramt Rohrbach, 1973)
Keywords: rohrbach

Quatre ans de recherches archéologiques à l'Abbaye de Dommartin - Pontroue, Pierre (Bulletin de la Commission Départementale des Monuments Historiques du Pas-de-Calais, 1973)
Keywords: dommartin

Kloster Oelinghausen. Zur 800. Wiederkehr des Gründungsjahres - Richtering, Helmut (Westfälische Zeitschrift, 1973)
Keywords: oelinghausen

Philip of Harvengt's contribution to the question of passage from one religious order to another - Roby, Douglass (Analecta Praemonstratensia, 1973)
Keywords: 👤 philip of harvengt

Die Marienkrönung des Waltensburger Meisters in Churwalden - Rutishauser, Hans (Unsere Kunstdenkmäler : Mitteilungsblatt für die Mitglieder der Gesellschaft für Schweizerische Kunstgeschichte, 1973)
Keywords: churwalden

L'architecture de l'abbaye de Saint-Jean d'Amiens - Sartre, Josiane (Bulletin de la Société des Antiquaires de Picardie, 1973)
Keywords: amiens

Weissenau, Pfarrkirche. Ehemalige Prämonstratenser-Abteikirche - Schnell, Hugo (Kleine Kunstführer, 1973)
Keywords: weissenau

Kloster Arnstein an der Lahn - Siedenkamp, Gerhard (Klosterverwaltung Kloster Arnstein, 1973)
Keywords: arnstein

Titchfield Abbey and St. Peter's Church, Titchfield - Sleep, E. E. (Environmental Studies Leaflet, 1973)
Keywords: titchfield (st peter's)

Standaardmolen Ter Rijst - Smet, L. (Molenecho's, 1973)
Keywords: molen ter rijst

Kloster Schäftlarn - Solf, Hugo (Schnell & Steiner, 1973)
Keywords: schäftlarn

Les premières chartes de l'abbaye de Silly-en-Gouffern (1150-1250) - Talabardon, Catherine (Bulletin de la Société Historique et Archéologique de l'Orne, 1973)
Keywords: silly

Les premières chartes de l'abbaye de Silly-en-Gouffern (Orne), 1150-1250 - Talabardon, Catherine (Positions des thèses de l'École des Chartes, 1973)
Keywords: silly

Acta et decreta Capitulorum Generalium Ordinis Praemonstratensis 3: 1531 - 1571 - Valvekens, Johannes B. (Abbatia Averbodiensis, 1973)
Keywords: ⚖️ chapters and statutes

Un catalogue des manuscrits de Parc rédigé sous Joseph II - Van Balberghe, Emile (Analecta Praemonstratensia, 1973)
Keywords: park

Antiphonale Missarum Praemonstratense - Weyns, Norbert J. (Bibliotheca Analectorum Praemonstratensium, 1973)
Keywords: 🛐 liturgy

De geestelijke geschiedenis van de Premonstratenzers in de Lage Landen - Weyns, Norbert J. (De glans van Prémontré oude kunst uit witherenabdijen der Lage Landen : tentoonstellingscatalogus : Abdij van Park-Heverlee, 15 september - 11 november 1973, 1973)
Keywords: 🇳🇱 netherlands (general)

A mediaeval belt shape from Holywood Abbey, Dumfriesshire - Williams, James (Transactions of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1973)
Keywords: holywood

Monasterio premonstratense de Urdax II - Zudaire Huarte, Eulogio (Analecta Praemonstratensia, 1973)
Keywords: urdax

Die ältesten Urkunden und die frühe Geschichte des Prämonstratenserstiftes Cappenberg in Westfalen (1122 bis 1200). Erster Teil: Urkundenkritik - Petry, Manfred (Archiv für Diplomatik, Schriftgeschichte, Siegel- und Wappenkunde, 1972)
Article Die ältesten Urkunden und die frühe Geschichte des Prämonstratenserstiftes Cappenberg in Westfalen (1122 bis 1200). Erster Teil: Urkundenkritik was published on Dec 1972 in the journal Archiv für Diplomatik, Schriftgeschichte, Siegel- und Wappenkunde (Volume 18, Issue JG).
Keywords: cappenberg

1161. Schenking van het altaar van Broechem en zijn afhankelijkheden Oelegem en Wijnegem aan de abdij van Tongerlo. - Spruyt, A. (Tijdschrift van de Heemkundige Kring Jan Vleminck Wijnegem, 1972)
Keywords: tongerlo

850-Jahrfeier des Prämonstratenserordens in Clarholz - Meier, Johannes (Gütersloher Beiträge zur Heimat- und Landeskunde, 1972)
Keywords: clarholz

A propósito de los premonstratenses españoles - Backmund, Norbert (Yermo: Cuadernos de historia y de espiritualidad monasticas, 1972)
Keywords: 🇪🇸 spain (general)

Die mittelalterlichen Geschichtsschreiber des Prämonstratenserordens - Backmund, Norbert (Bibliotheca Analectorum Praemonstratensium, 1972)
Keywords: 📚 premonstratensian (general)

Ein Profeßbuch des Klosters Windberg - Backmund, Norbert (Ostbairische Grenzmarken, 1972)
Keywords: windberg

A somlóvásárhelyi premontrei apácák (A szegedi Szentlélek- és a bécsi Porta Coeli-kolostor között) - Bálint, Sándor (A Veszprém megyei múzeumok közleményei, 1972)
Keywords: himmelspforte (austria); somlóvásárhely; szeged

Ilbenstadt: Geschichte der Praemonstratenserabtei - Bewerunge, Norbert (Große Baudenkmäler, 1972)
Keywords: ilbenstadt

Arthous et Hastingues en Gascogne - Dézélus, Robert (Marrimpouey, 1972)
Keywords: arthous

Zur Archivgeschichte des Klosters Adelberg - Fischer, Joachim (Zeitschrift für Württembergische Landesgeschichte, 1972)
Keywords: adelberg

Les anciennes paroisses prémontrées du diocèse de Sées (II) - Fournée, Jean (Bulletin de la Société Historique et Archéologique de l'Orne, 1972)
Keywords: 🇫🇷 france (general)

Das Prämonstratenserkloster zu Kaiserslautern - Friedel, Heinz (Heimatkalender für die Stadt und den Landkreis Kaiserslautern, 1972)
Keywords: kaiserslautern

Un fragment d'un tympan provenant de l'Abbaye de la Case-Dieu - Gabriel, Astrik Ladislas (Analecta Praemonstratensia, 1972)
Keywords: case dieu

Herman van Doornik en Norbertus - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1972)
Keywords: 👤 norbert of xanten

Het Polenprivilege van Norbertus, 4 juni 1133 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1972)
Keywords: 👤 norbert of xanten

Norbertus en de brand te Kamerijk in 1123 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1972)
Keywords: 👤 norbert of xanten

Kloster und Klosterkirche Enkenbach - Haffner, Franz (Kath. Pfarramt St. Norbert, 1972)
Keywords: enkenbach

"Das Haus des Lichtes" - "das Haus des neuen Lichtes". Prämonstratenser und Kreuzritter in Ter Apel - Hoffmann, Lingen (Jahrbuch des Emsländischen Heimatbundes, 1972)
Keywords: ter apel

St. Peter in Merzig - Klewitz, Martin (Rheinische Kunststätten, 1972)
Keywords: merzig

Ein Annalenfragment und die Datierung der Arnsteiner Bibel in London - Köllner, Herbert (Scriptorium, 1972)
Keywords: arnstein

A propos des codes législatifs de prémontré durant le XIIe siècle - Lefèvre, Placide (Analecta Praemonstratensia, 1972)
Keywords: ⚖️ chapters and statutes

Travaux de maîtres louvanistes pour l'abbaye d'Averbode depuis le XIVe au XVIIIe siècle - Lefèvre, Placide (Arca lovaniensis : artes atque historiae reserans documenta, 1972)
Keywords: averbode

L'abbaye d'Arthous - Lemort, André (Les monuments historiques de la France, 1972)
Keywords: arthous

De oude glasramen van de Abdij van 't Park te Heverlee - Maes, F. (Jaarboek van de geschied- en oudheidkundige kring voor Leuven en omgeving, 1972)
Keywords: park

De bisschoppelijke stichtingsoorkonden voor O.L. Vrouwkapittel en Sint-Michielsabdij te Antwerpen (1124) - Mingroot, Erik van (Analecta Praemonstratensia, 1972)
Keywords: antwerp

De stichtingsoorkonde van de abdij Tongerlo: echt of vals? - Mingroot, Erik van (Archives et bibliothèques de Belgique, 1972)
Keywords: tongerlo

L'ancienne abbaye de Chambrefontaine, sa fondation, son domaine au XIIIe siècle - Moreau, Jean-Paul (Bulletin d'information - Société d'histoire et d'archéologie de la Goele, 1972)
Keywords: chambrefontaine

The Annals of Connacht and Loch Cé and the Monasteries of Boyle and Holy Trinity - O'Dwyer, B.W. (Proceedings of the Royal Irish Academy: Archaeology, Culture, History, Literature, 1972)
Keywords: lough key

Die Abtwahl im Stift Wilten von der Gründung bis zur Beendigung des Exemtionsstreites - Palme, Rudolf (Analecta Praemonstratensia, 1972)
Keywords: wilten

Milon de Sélincourt, évêque de Thérouanne - Petit, François (Analecta Praemonstratensia, 1972)
Keywords: 📚 premonstratensian (general)

Les prémontrés à Arthous (1160-1791) - Peyrous, Bernard (Analecta Praemonstratensia, 1972)
Keywords: arthous

Capgrave's Life of St. Norbert: direction, dialect and spelling - Smetana, Cyril Lawrence; Colledge, Edmund (Mediaeval Studies, 1972)
Keywords: 👤 john capgrave; 👤 norbert of xanten

Bernardus Fontis Calidi, abbas O. Praem., et errores sui temporis - Valvekens, Johannes B. (Analecta Praemonstratensia, 1972)
Keywords: fontcaude

Ehemalige Kloster- und heutige Pfarrkirche Füssenich mit Alderikus-Sarkophag - Van Der Broeck, Heribert (Heimatjahrbuch des Kreises Düren, 1972)
Keywords: füssenich

Die Gründungszeit des Prämonstratenserstiftes Hamborn - Wolter, Heinz (Annalen des Historischen Vereins für den Niederrhein, 1972)
Keywords: hamborn

Campomanes, desamortizador del monasterio premostratense de Urdax - Zudaire Huarte, Eulogio (Hispania sacra. Revista española de historia eclesiástica, 1972)
Keywords: urdax

Monasterio premonstratense de Urdax I - Zudaire Huarte, Eulogio (Analecta Praemonstratensia, 1972)
Keywords: urdax

Gedenkboek Orde van Prémontré, 1121-1971 (Altiora, 1971)
Keywords: 📚 premonstratensian (general)

Ein Profeßbuch des Klosters Windberg - Backmund, Norbert (Ostbairische Grenzmarken, 1971)
Keywords: windberg

Anselm of Havelberg, his life and works - Bierlein, Raymond Eugene (Western Michigan University, 1971)
Keywords: 👤 anselm of havelberg

Over Servatius, de stichter van 'Sint Catharinadal' - Broeders, J. H. M. (Jaarboek van de geschieden oudheidkundige Kring van stad en land van Breda "De Oranjeboo", 1971)
Keywords: sint-catharinadal

Abtei Wedinghausen - Propsteikirche St. Laurentius Arnsberg - Brüggemann, Clemens (Städtekundliche Schriftenreihe über die Stadt Arnsberg, 1971)
Keywords: wedinghausen

The Bible of Floreffe: Redating of a Romanesque Manuscript - Chapman, Gretel (Gesta, 1971)
Keywords: floreffe

Lomer: A Study of a Deserted Medieval Village - Collins, Frances; Oliver, J. (Proceedings of the Hampshire Field Club and Archaeological Society, 1971)
Keywords: lomer

Norbertijnerabdij St. Cornelius en Cyprianus te Ninove - Coppens, Cyprianus (Analecta Praemonstratensia, 1971)
Keywords: ninove

O niektórych źródłach do historii zakonu premonstrateńskiego w Polsce w XII i XIII wieku - Deptuła, Czesław (Archiwa, Biblioteki i Muzea Kościelne, 1971)
-
Keywords: 🇵🇱 poland (general)

Les Cisterciens de Vauclair et les Prémontrés de Cuissy en litige au sujet d'un bois - Dimier, Anselme (Analecta Praemonstratensia, 1971)
Keywords: cuissy

Une donation de l'abbaye de Saint-Antoine à l'abbaye de Prémontré - Dimier, Anselme (Analecta Praemonstratensia, 1971)
Keywords: prémontré

Une donation de Louis VIII aux Prémontrés de Bellozanne - Dimier, Anselme (Analecta Praemonstratensia, 1971)
Keywords: bellozanne

Une lettre de saint Louis en faveur des abbayes de Valsery et de Lieu-Restauré - Dimier, Anselme (Analecta Praemonstratensia, 1971)
Keywords: lieu-restauré; valsery

Chotěšovský kopiář v Řezně a vysazení Touškova roku 1311 - Dolista, Karel (Minulostí západočeského kraje, 1971)
Keywords: chotěšov

Der Grundbesitz des Stiftes Wilten in Südtirol bis ins 18. Jahrhundert - Ebnicher, Gottfried (University of Innsbruck, 1971)
Keywords: wilten

The Premonstratensians and the "Drang Nach Dem Osten" - Epp, George (St Norbert's College, 1971)
Keywords: 📚 premonstratensian (general)

Abadía de Santa María de Bellpuig de les Avellanes (Lérida) - Ferrari Nuñez, Angel (Boletín de la Real Academia de la Historia, 1971)
Keywords: bellpuig de las avellanes

L'Abbaye de Belle-Étoile: étude archéologique - Fournée, Jean (Art de Basse-Normandie, 1971)
Keywords: belle-étoile

The role of the canons of Prémontré in the intellectual movements of the twelfth and thirteenth centuries - Gabriel, Astrik Ladislas (Gedenkboek Orde van Prémontre, 1121-1971, 1971)
Keywords: 📚 premonstratensian (general)

Inventaris van het archief van het Norbertinessenklooster van Sint-Gerlach - Haas, J.A.K (Rijksarchief in Limburg, 1971)
Keywords: sint-gerlach

Prämonstratenserkloster- und Pfarrkirche Speinshart - Hartig, Michael (Kleine Kunstführer, 1971)
Keywords: speinshart

La fondation de l'Abbaye Prémontrée d'Humilimont entre 1136 et 1141 - Jordan, Joseph (Zeitschrift für schweizerische Kirchengeschichte, 1971)
Keywords: humilimont

Les antiennes empruntées aux Livres des Rois dans la liturgie de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1971)
Keywords: 🛐 liturgy

Les archives de l'abbaye des Prémontrés d'Averbode à la fin de l'Ancien Régime - Lefèvre, Placide (Archives et bibliothèques de Belgique, 1971)
Keywords: averbode

Les tombeaux des abbés d'Averbode du 13e au 19e siècle - Lefèvre, Placide (Analecta Praemonstratensia, 1971)
Keywords: averbode

Un problème d'ordre archivéconomique à propos de deux actes du XIIIe siècle - Lefèvre, Placide (Analecta Praemonstratensia, 1971)
Keywords: averbode

L'abbaye Notre-Dame de Dilo - Lemaire, Roger (L'Echo de Joigny: Revue de l'Association Culturelle et d'Etudes de Joigny, 1971)
Keywords: dilo

De abdijkerk van Postel - Leurs, Stan (Noordgouw, 1971)
Keywords: postel

Studien zu den Urkunden und zur Geschichte des Prämonstratenserklosters Steingaden von seiner Gründung im Jahre 1147 bis 1240 - Liebel, Johanna (Ludwig-Maximilians-Universität, 1971)
Keywords: steingaden

Premonstratenserklosteret i Tønsberg St. Olavs kirke - Nordens største rundkirke - Lunde, O. (Vestfoldminne, 1971)
Keywords: tønsberg

Lametz ou les Mares ? A propos de l'ancienne abbaye de Prémontrés Catégorie - Marchand, Jean (Revue Historique Ardennaise, 1971)
Keywords: longwé

Der Westturm der Marienkirche in Gelnhausen - Nothnagel, Karl (Staufische Architektur in Gelnhausen und Worms, 1971)
Keywords: gelnhausen (marienkirche)

Die Peterskirche in Gelnhausen - Nothnagel, Karl (Staufische Architektur in Gelnhausen und Worms, 1971)
Keywords: gelnhausen (peterskirche)

Nová Říše - Nováková-Skalická, Miroslava (Kraj. středisko st. památkové péče a ochrany přírody, 1971)
Keywords: nová říše

Die Abtwahl im Stift Wilten von der Gründung bis zur Beendigung des Exemtionsstreites (IV) - Palme, Rudolf (Analecta Praemonstratensia, 1971)
Keywords: wilten

De kerk van St. Catharinadal te Breda - Peeters, C. J. A. C. (Jaarboek van de geschieden oudheidkundige Kring van stad en land van Breda "De Oranjeboo", 1971)
Keywords: sint-catharinadal

Het klooster van Serskamp gezeid "Tussenbeke" - Pieters, J. (Heemkundig tijdschrift uitgegeven door de Heemkring Jan Broeckaert, 1971)
Keywords: tussenbeek

De premonstratenzer koorzusters: van dubbelkloosters naar autonome konventen - Schijndel, Th. M. van (Gedenkboek Orde van Prémontré, 1121–1971, 1971)
Keywords: 📚 premonstratensian (general)

Die gefälschten Urkunden des Bischofs Reginbert von Brixen für das Kloster Wilten - Steinegger, Fritz (Beiträge zur Geschichte Tirols Festgabe des Landes Tirol zum Elften Österreichischen Historikertag in Innsbruck vom 5. bis 8. Oktober 1971, 1971)
Keywords: wilten

Prämonstratenser-Chorherrenstift Wilten und Land Tirol - Steinegger, Fritz (Südtirol in Wort und Bild, 1971)
Keywords: wilten

Odo Rigaldus et Ordo Praemonstratensis - Valvekens, Johannes B. (Analecta Praemonstratensia, 1971)
Keywords: 📚 premonstratensian (general)

Ancienne abbaye de Basse Fontaine - Vautrin, Paul (La vie en Champagne, 1971)
Keywords: basse fontaine

Reconstructie van de vroegere indeling der kloosterkerk van St.-Catharinadal te Breda - Veken, C. J. M. van der (Jaarboek van de geschieden oudheidkundige Kring van stad en land van Breda "De Oranjeboo", 1971)
Keywords: sint-catharinadal

Houses of Premonstratensian canons: Abbey of Halesowen - Willis-Bund, J.W.; Page, William (A History of the County of Worcester, 1971)
Keywords: halesowen

Kapelle, Kloster und Hof zu Wülfersberg - Winnen, August (Heimatjahrbuch des Landkreises Neuwied, 1971)
Keywords: wülfersberg

Vom früheren Reichtum und einigen Kirchen des Klosters Pöhlde - Zander, Otto (Allgemeiner Harz-Berg-Kalender, 1971)
Keywords: pöhlde

Restaurierung des historischen Taubenturms auf Birelerhof - J.B. (Luxemburger Wort, 1970)
Keywords: birelerhof

Dodford Priory, Near Bromsgrove (SO/728933) - Aston, Michael A. (Worcestershire Archaeology and Local History Newsletter, 1970)
Keywords: dodford

Pencaitland Parish Church - Barker, R.W. (1970)
Keywords: pencaitland

Halesowen Abbey Guest House, Site (SO/97568283) - Bond, C. James (Worcestershire Archaeology and Local History Newsletter, 1970)
Keywords: halesowen

L'obituaire de Saint-Jean d'Amiens - Brouette, Émile (Bulletin de la Société des Antiquaires de Picardie, 1970)
Keywords: amiens

Précisions sur la matricule des abbés de Floreffe au moyen âge. - Brouette, Emile (Analecta Praemonstratensia, 1970)
Keywords: 🇫🇷 france (general)

De pachthoven en de watermolen van de abdij van Park te Bertem - De Kempeneer, Joseph (Mededelingen van de Geschied- en Oudheidkundige Kring voor Leuven en Omgeving, 1970)
Keywords: park

Het register der beneficiën en kerken van de abdij van Park - De Kempeneer, Joseph (Mededelingen van de Geschied- en Oudheidkundige Kring voor Leuven en Omgeving, 1970)
Keywords: park

Saint Louis et les Prémontrés - Dimier, Anselme (Analecta Praemonstratensia, 1970)
Keywords: 📚 premonstratensian (general)

Der Ratzeburger Dom und die Frage nach der Farbigkeit romanischer Backsteinkirchen zwischen Niedersachsen und Seeland - Ellger, Dietrich (Nordelbingen, 1970)
Keywords: ratzeburg

Das Westportal der Prämonstratensernonnenkirche Enkenbach - Fath, Manfred (Pfälzer Heimat, 1970)
Keywords: enkenbach

Les anciennes paroisses prémontrées du diocèse de Sées (I) - Fournée, Jean (Bulletin de la Société Historique et Archéologique de l'Orne, 1970)
Keywords: 🇫🇷 france (general)

Akten van Oudenbiezen in het archief van Averbode - Gerits, Trudo (Limburg, 1970)
Keywords: averbode

L'abbaye de Dileghem des origines au XVe siècle - Glade, J. (University of Brussels, 1970)
Keywords: dieleghem

Quedlinburg, Schloßberg, Stiftsberg und Wipertikirche - Grimm, Paul (Exkursionsführer: Exkursion vom 29. August bis 5. September 1970 ; II. Internationaler Kongreß für Slawische Archäologie, Berlin 24.-28. August 1970, 1970)
Keywords: quedlinburg

Streiflichter auf die Geschichte des Havelberger Domes - Hoffmann-Aleith, Eva (Dom zu Havelberg: 1170-1970, 1970)
Keywords: havelberg

L'abbaye de Corneux - Jouvenot (s.n., 1970)
Keywords: corneux

Statuty Kapituły Norbertańskiej z r. 1340: w tłumaczeniu polskim z r. 1541 - Karaś, Mieczysław; Perzanowski, Zbigniew (Zeszyty naukowe Uniwersytetu Jagiellońskiego, 1970)
Keywords: ⚖️ chapters and statutes

Der Wiltener Kelch. Ein von Bertold III. von Andechs gestiftetes Kunstwerk des 12. Jahrhunderts - Kraut, Alfred (Lech-Isar-Land. Organ des Heimatverbandes Lech-Isar-Land e. V., 1970)
Keywords: wilten

L'Office du Noël et de son octave dans la liturgie de Prémontré - Lefèvre, Placide (Analecta Praemonstratensia, 1970)
Keywords: 🛐 liturgy

Les antiennes du vendredi après les Cendres dans la liturgie de Prémontré - Lefèvre, Placide (Questions liturgiques, 1970)
Keywords: 🛐 liturgy

Besaß Enkenbach eine "Doppelklosterkirche" ? Einflüsse der Klausur auf die Architektur - Lutz, Karl (Jahrbuch zur Geschichte von Stadt und Landkreis Kaiserslautern, 1970)
Keywords: enkenbach

Over het archief van de voormalige Abdij Sint Marienweerd bij Beesd - Maris, A.J. (Nederlands Archievenblad, 1970)
Keywords: mariënweerd

Clarholz in der Ordensgeschichte der Prämonstratenser - Meyer, Johannes (Westfalen - Hefte für Geschichte, Kunst und Volkskunde. Mitteilungen des Vereins für Geschichte und Altertumskunde Westfalens, des LWL-Landesmuseums für Kunst und Kulturgeschichte, des LWL-Amts für Denkmalpflege in Westfalen und des LWL-Museums für Archäologie, 1970)
Keywords: clarholz

Birgittatraditionen från Prag bland handskrifterna i Stift Schlägl, Oberösterreich - Nyberg, Tore (Nordisk tidskrift för bok- och biblioteksväsen, 1970)
The St. Birgitta textual tradition from Prague in manuscripts of the monastery at Schlägl in Upper Austria.
Keywords: schlägl

Die Abtwahl im Stift Wilten von der Gründung bis zur Beendigung des Exemtionsstreites - Palme, Rudolf (Analecta Praemonstratensia, 1970)
Keywords: wilten

Une flambée monastique au XIIe siècle: les ordres de Cîteaux et de Prémontré en Lorraine. - Parisse, Michel (Cahiers lorrains, 1970)
Keywords: 🇫🇷 france (general)

Tongerlo en zijn studenten op het keerpunt van de middeleeuwen en de moderne tijden - Ridder-Symoens, Hilde de; Milis, Ludo (Ons geestelijk erf, 1970)
Keywords: tongerlo

Notes sur les origines de l'abbaye de Lahonce - Romatet, Jacques (Bulletin du Musée Basque, 1970)
Keywords: lahonce

Le cartulaire du prieuré du Val-des-Lys (Leliëndaal) à Hombeek - Rouhart-Chabot, Juliette (Handelingen van de Koninklijke Kring voor Oudheidkunde, Letteren en Kunst van Mechelen = Bulletin du Cercle Archéologique, Littéraire et Artistique de Malines, 1970)
Keywords: leliëndaal

A tomb-slab in Gullane church - Ryan, A.; Ryan, N. (Transactions of the East Lothian Antiquarian and Field Naturalists' Society, 1970)
Keywords: gullane

Zur Literatur über Havelberg und des Havelberger Dom - Schirge, Alfred (Dom zu Havelberg: 1170-1970, 1970)
Keywords: havelberg

Histoire de l'Abbaye royale de Notre Dame de Septfontaines en Thierache: des villages de Fagnon, Neuville-les-This, This, Sury, Gruyeres et des hameaux de la Forge-Maillart et Écogne - Sery, Jean (s.n., 1970)
Keywords: septfontaines en thiérache

Die Klosterkirche in Enkenbach, ihre Baugeschichte und ihre künstlerische Bedeutung. Zum 700jährigen Jubiläum der Kirche - Stich, Fritz (Jahrbuch zur Geschichte von Stadt und Landkreis Kaiserslautern, 1970)
Keywords: enkenbach

Deux manuscrits de Parc retrouvés - Van Balberghe, Emile (Analecta Praemonstratensia, 1970)
Keywords: park

Fragmenta Parcensia. A propos d'un fragment de la chronique dite de Saint Jérôme - Van Balberghe, Emile (Archives et bibliothèques de Belgique, 1970)
Keywords: park

Een klooster uit het Brabants-Hollandse rivierengebied. De abdij Berne en haar materiële betekenis in de Middeleeuwen - Van Dijk, H. (Afdeling Agrarische Geschiedenis Landbouwhogeschool Wageningen, 1970)
Keywords: berne

Filips van Harveng, (ca. 1100-1183), abt, schrijver - Weyns, Norbert J. (Nationaal biografisch woordenboek, 1970)
Keywords: bonne-espérance; 👤 philip of harvengt

E cinere phoenix: Renaissance de Bellelay, 1142-1960 - Wyss, Alfred; Kohler, Simon (Editions du Jura, 1970)
Keywords: bellelay